2020
DOI: 10.21203/rs.3.rs-73870/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gene Therapy for Aromatic L-Amino Acid Decarboxylase Deficiency by MR-Guided Direct Delivery of AAV2-AADC to Midbrain Dopaminergic Neurons

Abstract: Background: Aromatic L-amino acid decarboxylase (AADC) deficiency is a rare genetic disorder characterized by deficient synthesis of dopamine and serotonin. It presents in early infancy, and causes severe developmental disability and lifelong motor, behavioral, and autonomic symptoms including oculogyric crises (OGC), sleep disorder, and mood disturbance.Objective: We investigated the safety and efficacy of delivery of a viral vector expressing AADC (AAV2-hAADC) to the midbrain in children with AADC deficiency… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…When available, imaging data showed more prominent increase in radiotracer uptake in regions that correlate with areas of infusions. FMT-PET putaminal uptake ( 33 ) or 18F-DOPA PET midbrain, putaminal, and caudate uptake ( 34 ) passed from absent to bilaterally present with high signal intensity, after up to 2-year follow-up, while in the study from Hwu and coll ( 31 ) three out of four participants showed an increased 18F-DOPA uptake, as compared to pre-treatment imaging ( Table 6 ). CSF catechol analysis demonstrated levels that trended toward increased dopamine metabolites across these studies, but degree of change in serotonin metabolites and levodopa varied significantly across individuals both before and after treatment.…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…When available, imaging data showed more prominent increase in radiotracer uptake in regions that correlate with areas of infusions. FMT-PET putaminal uptake ( 33 ) or 18F-DOPA PET midbrain, putaminal, and caudate uptake ( 34 ) passed from absent to bilaterally present with high signal intensity, after up to 2-year follow-up, while in the study from Hwu and coll ( 31 ) three out of four participants showed an increased 18F-DOPA uptake, as compared to pre-treatment imaging ( Table 6 ). CSF catechol analysis demonstrated levels that trended toward increased dopamine metabolites across these studies, but degree of change in serotonin metabolites and levodopa varied significantly across individuals both before and after treatment.…”
Section: Resultsmentioning
confidence: 98%
“…Out of the 1,437 studies derived from the initial searching strategy ( Figure 1 ), 27 published articles met full criteria ( 8 34 ) ( Tables 1 – 6 ) and underwent data extraction and assessment for individual risk of bias. There were 21 studies focusing on PD ( 8 28 ), two on HD ( 29 , 30 ), and four on AADC deficiency ( 31 34 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations